UNITARY EQUIVALENCE OF UNILATERAL OPERATOR VALUED WEIGHTED SHIFTS WITH QUASI-INVERTIBLE WEIGHTS - Orovčanec, Marija (Matematichki Bilten, 1993)
In this paper we consider the problem of unitary equivalence of unilateral operator valued weighted shifts with quasi-invertible weights.